Secondary English Textbooks of Nepal: Reservoir of Structures or Bearer of Critical Consciousness? - Thapa, Rudra Bahadur (Kanakai Journal, 2024)
Textbooks are an integral part of everyday teaching in Nepalese classrooms. They mirror the objectives mentioned in several policy documents at the National level. The Constitution of Nepal, the School Sector Development Plan, and the National Objectives of Education all strive to develop conscientious individuals by eliminating all forms of discrimination prevalent in the country. This study reveals how much the secondary English textbook of Nepal supports achieving those goals. This critical content analysis aims to explore the presence of texts from the perspective of critical pedagogy. This study has analyzed the secondary English textbook of grade 9 published by the Curriculum Development Centre, Nepal. For analysis, five different critical themes were ascertained on the basis of the literature review. The reading texts present in the book were examined against it. The finding revealed an inadequate presence of critical texts (27.77%) in the grade 9 English textbook. Instead of developing critical consciousness in students, the textbook looks more like a practice book for different linguistic structures. The students are less likely to change, challenge, and contest perceived inequity through the book.